Taxonomic revision of Australian Platynectes Régimbart, 1879 (part I)—four new species from Queensland (Coleoptera: Dytiscidae, Agabinae) - Hendrich, Lars; Šťastný, Jaroslav (Zootaxa, 2014)
Four species of the genus Platynectes subgenus Gueorguievtes Vazirani, 1976 are described from Queensland, Australia: Platynectes brancuccii sp. n. (Atherton Tableland), P. larsoni sp. n. (Mulgrave Range and Windsor Tableland), P. ponderi sp. n. (Carnarvon Range) and Platynectes weiri sp. n. (White Mountains National Park and Hope Vale Mission). The latter two are the first species of the genus with striae on elytra and the informal P. weiri-species group is established for them. Platynectes brancuccii sp. n. and P. larsoni sp. n. belong to the P. decempunctatus-species group. All four species were collected from small rain forest streams or rest pools of intermittent creeks. Important species characters (median lobes, parameres and colour patterns) of all species are figured, and notes on their distribution and ecology are given. Altogether 17 species of the genus are now known from Australia.